The Concept of Religious Moderation: A Study of Maudhu’i’s Interpretation - Rifki Azkya Ramadhan; Nurul Fadhilah Ramadhani Arqam; Asep Abdul Muhyi (Bulletin of Islamic Research, 2024)
This study aims to explore the concept of religious moderation from the perspective of Islam through a descriptive analysis approach. In this context, religious moderation is interpreted as a balanced attitude that encompasses various aspects of religious life. The results of the descriptive analysis of the Qur'an and relevant Islamic literature identify that religious moderation in Islam embodies values such as simplicity, tolerance, and justice. The Islamic perspective on religious moderation is reflected in the teachings of the Qur'an and Sunnah, emphasizing the importance of avoiding extremism and fanaticism in religious practice. In the Qur'an, religious moderation is represented by the phrase "ummatan wasathan" in QS. Al-Baqarah verse 143, signifies the attitude of tawazun, or balance, as a distinguishing feature of the community of Prophet Muhammad SAW, characterized by fairness, wisdom, and impartiality. This balanced approach applies to all aspects of life, including worldly and otherworldly affairs, which must always remain balanced. Moderate attitudes in religious life are crucial to stop intolerant behavior that can lead to discrimination. In Indonesia, with its multicultural society, it is important to maintain harmony by adhering to the values of Islamic tolerance. This will ensure that religious life remains harmonious without any discrimination against fellow believers.